Solely Cellulose-based Adsorbent Derived from Oil Palm Empty Fruit Bunches for Dye Removal - Athanasia Amanda Septevani; Farhan Riza Afandi; Yulianti Sampora; Melati Septiyanti; Yenni Apriliany Devy; Aisah Resti Amelia; Dian Burhani (Reaktor, 2020)
The purpose of this research is to determine the adsorption capability of micro and nano-cellulose derived from oil palm empty fruit bunch (EFB) as dye removal. Cellulose based adsorbents were successfully obtained from EFB in the form of microcellulose (eMC) via both delignification (D-eMC) and bleaching processes (B-eMC) as well as in nanocellulose (eNC) by using acid hydrolysis method and hence termed as delignified-eNC (D-eNC) and bleached-eNC (B-eNC) respectively. Dye adsorption test was carried out by UV-Spectrophotometer by comparing initial dye MO concentration (as a control solution) to the treated MO solution upon the addition of micro- and nano- cellulose based adsorbent. It was clear that the dye removal efficiency of micro-cellulose both D-eMC and B-eMC were lower than the nano-cellulose structures. The higher adsorptive capacity of nano-size cellulose compared to the micro-size cellulose was confirmed by the distinct presence of FTIR shifting peak of hydroxyl and sulfonyl groups. It was expected as the micro-size of cellulose would not be able to provide a good adsorptive capability of hydroxyl surface active agent to adsorb the dye. In the case of eNC, the result showed that D-eNC afforded a better dye adsorption than B-eNC. At the same concentration of eNC at 3 wt. %, D-eNC could adsorb at about 19.3% of MO while only 2.4% of MO could be removed by B-eNC. Finally, all of adsorbent could maintain pH and TDS within water quality specification.